2019
DOI: 10.1161/circheartfailure.119.006067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hemodynamic Ramp Test-Guided HVAD Speed and Medication Adjustments on Clinical Outcomes

Abstract: Background: Hemodynamic ramp (HR) tests can guide the optimization of left ventricular assist device (LVAD) speed and direct medical therapy. We investigated the effects of HR-guided LVAD management. Methods and Results: This prospective, multicenter, randomized, pilot study compared outcomes in LVAD patients using an HR-guided (HR group) versus a standard transthoracic echocardiography-guided (control group) management strategy. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 25 publications
3
68
0
Order By: Relevance
“…We fully agree that the PAP‐guided adjustment of LVAD speed and medications would likely result in a reduction in HF readmissions, given the strongly positive studies previously published on the use of CardioMEMS in general HF cohorts . If the CardioMEMS device can be mechanistically linked to LVADs, the promising future of a smart pump, which can automatically adjust pump settings based on feedback from the CardioMEMS, would be a welcomed innovation. Unique hemodynamic challenges remain nevertheless in estimating the degree of ventricular unloading, as approximately half of clinically stable LVAD patients have decoupling between diastolic PAP and pulmonary capillary wedge pressure …”
mentioning
confidence: 53%
See 1 more Smart Citation
“…We fully agree that the PAP‐guided adjustment of LVAD speed and medications would likely result in a reduction in HF readmissions, given the strongly positive studies previously published on the use of CardioMEMS in general HF cohorts . If the CardioMEMS device can be mechanistically linked to LVADs, the promising future of a smart pump, which can automatically adjust pump settings based on feedback from the CardioMEMS, would be a welcomed innovation. Unique hemodynamic challenges remain nevertheless in estimating the degree of ventricular unloading, as approximately half of clinically stable LVAD patients have decoupling between diastolic PAP and pulmonary capillary wedge pressure …”
mentioning
confidence: 53%
“…We read with great interest the protocol design of HEMO‐VAD pilot study proposed by Veenis and colleagues, in which the feasibility and implication of pulmonary artery pressure (PAP) guidance with CardioMEMS in patients with left ventricular assist device (LVAD) is prospectively investigated. Our team recently demonstrated the implications of hemodynamic optimization in LVAD patients, with the observed association of abnormal hemodynamics and heart failure (HF) readmissions along with hemocompatibility‐related adverse events …”
mentioning
confidence: 99%
“…Furthermore, given the complexity of the mechanism, simple supplementation of calories is not sufficient to improve cardiac cachexia. 24 Hemodynamic optimization via ramp test, 22 intravenous administration of testosterone to improve skeletal muscle wasting, 25 oral administration of omega-3 fatty acid to suppress chronic inflammation, 26 and cardiac rehabilitation might be effective to improve cardiac cachexia in LVAD patients. 27 Note: Variables were expressed as median and interquartile and compared between the groups using Mann-Whitney U test.…”
Section: F I G U R E Distribution Of Albumin Change During the First mentioning
confidence: 99%
“…Recently, Dr. Imamura and colleagues reported that aggressive hemodynamic optimization by right heart catheterization reduced various comorbidities and hospital readmission in LVAD patients [5,6]. Nevertheless, routine or repeated use of invasive hemodynamic assessment would not be recommended because of its specific complications such as infection, hemorrhage and its expensive medical cost as mentioned.…”
Section: The Authors Replymentioning
confidence: 99%